Optical switches materials and design - Chua, Soo-Jin; Li, Baojun, 1977- (Woodhead Publishing in materials., 2010)
Optical communication using optical fibres as the transmission medium is essential to handling the massive growth of both telecom and datacom traffic. To fully realize the potential bandwidth available on these optical fibres, other components of the optical network system have to be developed, ranging from detectors and multiplexers to buffers and switches. This book addresses the different technologies which can be applied to switching optical signals. An optical switch functions by selectively switching an optical signal delivered through an optical fibre or in an integrated optical.